2009
DOI: 10.1063/1.3270105
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gap defect states in organic bulk heterojunction solar cells from capacitance measurements

Abstract: Energy distributions ͓density-of-states ͑DOS͔͒ of defects in the effective band gap of organic bulk heterojunctions are determined by means of capacitance methods. The technique consists of calculating the junction capacitance derivative with respect to the angular frequency of the small voltage perturbation applied to thin film poly͑3-hexylthiophene͒ ͑P3HT͒ ͓6,6͔-phenyl C 61 -butyric acid methyl ester ͑PCBM͒ solar cells. The analysis, which was performed on blends of different composition, reveals the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
169
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 173 publications
(181 citation statements)
references
References 23 publications
12
169
0
Order By: Relevance
“…2(a) resulting from contributions of defect levels in the gap. We recently demonstrated that such defects belong to the polymer in analyzing P3HT diodes along with P3HT:PCBM solar cells [9]. Because a complete step is observed in ) ( f C , the inflection point serves to define a frequency m f related to the defect band kinetic response, which corresponds to the minimum of the frequency derivative Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2(a) resulting from contributions of defect levels in the gap. We recently demonstrated that such defects belong to the polymer in analyzing P3HT diodes along with P3HT:PCBM solar cells [9]. Because a complete step is observed in ) ( f C , the inflection point serves to define a frequency m f related to the defect band kinetic response, which corresponds to the minimum of the frequency derivative Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This band structure across the active layer differs from that expected using undoped materials, in which the potential drops linearly between the contacts [8]. Impedance and capacitance measurements have been used to evidence such band bending [9,10] usually exhibiting a Mott-Schottky characteristics ( V C  2 ), which can be readily interpreted as a strong indication of the presence of negatively charged defects within the P3HT energy gap.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations